Divergent Cotton leaf curl Multan betasatellite and three different alphasatellite species associated with cotton leaf curl disease outbreak in Northwest India - Kajal Kumar Biswas; Nenavath Balram; Marimuthu Elangovan; Supratik Palchoudhury; Utpal Kumar Bhattacharyya; Halima Khatoon; Shilpi Aggarwal; Shruti Godara; Pradeep Kumar; Satish Kumar Sain; Rupesh Arora; Sibnarayan Datta (PLoS ONE, 2025)
Cotton leaf curl disease (CLCuD) is a major constraint for production of cotton (Gossypium sp.) in Northwest India. CLCuD is caused by a monopartite, circular ssDNA virus belonging to the genus Begomovirus in association with betasatellites and alphasatellites, and ttransmitted by a whitefly vector (Bemisia tabaci). To explore the genetic variability in betasatellites and alphasatellite associated with the CLCuD-begomovirus complex in Northwest India. A survey was conducted for successive three years of 2014 to 2016 and twig samples from symptomatic and healthy cotton plants randomly were collected. Total plant DNAs were isolated, subjected to rolling circle amplification (RCA), cloning and sequencing. Full-length genome of 12 betasatellites and 13 alphasatellites, those were obtained in the present study, were analyzed. Sequence analysis showed that all the present betasatellites shared 85–99 percent nucleotide identity (PNI) among themselves and 84–95 PNI with other members of Cotton leaf curl Multan betasatellite (CLCuMB) and fell into one genogroup along with CLCuMB. But in close observation the present betasatellites clustered into two phylogenetic subgroups under single CLCuMB. The present alphasatellites showed 72–100 PNI among themselves and fell under three alphasatellite species, Gossypium Darwinii symptomless alphasatellite (GDarSLA), Cotton leaf curl Multan alphasatellite (CLCuMA) and Cotton leaf curl Burewala alphasatellite (CLCuBuA). In the recombination analysis, all the present betasatellites and alphasatellites were found to be recombinants involving intra species recombination in betasatellite, and interspecies recombination in alphasatellite species. The present study indicated that the betasatellite and alphasatellite molecules associated with CLCuD-begomovirus complex in Northwest India are genetically diverse.